Wiring the writing center - Hobson, Eric. (Logan, Utah : Utah State University Press, 1998)
As computers have brought important developments to composition studies, writing centers have found themselves creating and improvising applications for their own work and often for the writing programs and institutions in which they live. Online tutorials, websites with an array of downloadable resources for students, scheduling and email possibilities--all of these are becoming common-place among writing centers across the country. However, in spite of impressive work by individual centers, exchange on these topics between and among writing centers has been sporadic. As more writing centers.
The look and feel of the OWL Conference / Barbara Monroe -- Email "tutoring" as collaborative writing / David Coogan -- Reflection and responsibility in (cyber) tutor training : seeing ourselves clearly on and off the?screen / Rebecca Rickly -- WAC on the Web : writing center outreach to teachers of writing intensive courses / Sara Kimball -- Have you visited your online writing center today? : learning, writing, and teaching online at a community college / Clinton Gardner -- The other WWW : using intranets to reconfigure the who, when and where of network supported writing instruction / Kurt P. Kearcher -- Wiring a usable center : usability research and writing center practice / Stuart Blythe -- Drill pads, teaching machines, and programmed texts : origins of institutional technology in writing centers / Neal Lerner -- Virtual high school writing centers : a spectrum of possibilities / Pamela B. Childers, Jeannette Jordan, James K. Upton -- The community college mission and the electronic writing center / Ellen Mohr -- Random memories of the virtual writing center : the modes-to-nodes problem / Ray Wallace -- Computers in the writing center : a cautionary history / Peter Carino -- UnfURLed : 20 writing center sites to visit on the information highway / Bruce Pegg -- Computers and writing centers : an annotated bibliography / Steve Sherwood.
Includes bibliographical references (pages 231-241).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: English language -- Rhetoric -- Study and teaching -- Data processing; Report writing -- Study and teaching -- Data processing; English language -- Computer-assisted instruction; Report writing -- Computer-assisted instruction; Writing centers -- Automation; Rapports -- Rédaction -- Étude et enseignement -- Informatique; Rapports -- Rédaction -- Enseignement assisté par ordinateur; Centres de communication écrite -- Automatisation; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; English language -- Computer-assisted instruction; English language -- Rhetoric -- Study and teaching -- Data processing; Report writing -- Computer-assisted instruction; Report writing -- Study and teaching -- Data processing; Writing centers -- Automation; Electronic book